Apes and agriculture - Meijaard, Erik; Unus, Nabillah; Ariffin, Thina; Dennis, Rona; Ancrenaz, Marc; Wich, Serge; Wunder, Sven; Goh, Chun Sheng; Sherman, Julie; Ogwu, Matthew C.; Refisch, Johannes; Ledgard, Jonathan; et al. (Frontiers in Conservation Science, 2023)
Non-human great apes – chimpanzees, gorillas, bonobos, and orangutans – are threatened by agricultural expansion, particularly from rice, cacao, cassava, maize, and oil palm cultivation. Agriculture replaces and fragments great ape habitats, bringing them closer to humans and often resulting in conflict. Though the impact of agriculture on great apes is well-recognized, there is still a need for a more nuanced understanding of specific contexts and associated negative impacts on habitats and populations. Here we review these contexts and their implications for great apes. We estimate that within their African and South-East Asian ranges, there are about 100 people for each great ape. Given that most apes live outside strictly protected areas and the growing human population and increasing demand for resources in these landscapes, it will be challenging to balance the needs of both humans and great apes. Further habitat loss is expected, particularly in Africa, where compromises must be sought to re-direct agricultural expansion driven by subsistence farmers with small fields (generally <0.64 ha) away from remaining great ape habitats. To promote coexistence between humans and great apes, new approaches and financial models need to be implemented at local scales. Overall, optimized land use planning and effective implementation, along with strategic investments in agriculture and wildlife conservation, can improve the synergies between conservation and food production. Effective governance and conservation financing are crucial for optimal outcomes in both conservation and food security. Enforcing forest conservation laws, engaging in trade policy discussions, and integrating policies on trade, food security, improved agricultural techniques, and sustainable food systems are vital to prevent further decline in great ape populations. Saving great apes requires a thorough consideration of specific agricultural contexts.